1994
DOI: 10.1002/1097-0142(19941101)74:9<2430::aid-cncr2820740907>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathologic study of small flat colorectal carcinoma

Abstract: Background. Recent studies have noted that small flat carcinomas do exist in the human colon, but their clinicopathologic features have not been fully delineated. Methods. A clinicopathologic study of 62 flat colorectal carcinomas (FCC) and 80 polypoid colorectal carcinomas (PCC) was performed. FCC were defined for the study as colorectal adenocarcinomas confined to the mucosa or submucosa, macroscopically characterized as slightly elevated, often nearly flat, and sometimes with central shallow depressions. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 23 publications
(3 reference statements)
0
25
1
2
Order By: Relevance
“…Aggressive tumors are frequently associated with RASSF1A methylation in cancers of the thyroid and prostate Schagdarsurengin et al, 2002). Despite their small size, early flat colorectal tumors progress relatively quickly into deeply invasive tumors which frequently permeate the lymphatics and veins (Shimoda et al, 1989;Tada et al, 1994). Thus, a frequent RASSF1A methylation even in the early-stage tumor cases in our present study may be partly responsible for the aggressive clinical course associated with flat colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggressive tumors are frequently associated with RASSF1A methylation in cancers of the thyroid and prostate Schagdarsurengin et al, 2002). Despite their small size, early flat colorectal tumors progress relatively quickly into deeply invasive tumors which frequently permeate the lymphatics and veins (Shimoda et al, 1989;Tada et al, 1994). Thus, a frequent RASSF1A methylation even in the early-stage tumor cases in our present study may be partly responsible for the aggressive clinical course associated with flat colorectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Although not common, distinct morphological patterns and clinicopathological profiles of flat-type colorectal neoplasm have been well characterized. They are often associated with high-grade dysplasia from the early small flat but not exophytic mucosal lesions, and exhibit a relatively aggressive clinical behavior with a tendency to invade deep mucosal layers with lymphovascular permeation over a short time course (Shimoda et al, 1989;Tada et al, 1994). Since the early detection of such flat lesions is difficult compared with exophytic adenoma, they are often overlooked and tend to be found at a late stage of development.…”
Section: Introductionmentioning
confidence: 99%
“…49 Recent widespread use of screening colonoscopy, and use of new techniques designed to increase sensitivity, such as chromoendoscopy, 13,15,44 have increased the likelihood of detecting small noninvasive and invasive colorectal neoplasms. 23,25,34,40,44 Small invasive CRC (ie, those that are less than 1.0 cm in greatest diameter) have gained considerable attention recently primarily because some studies suggest these may be biologically different from usual ''large'' CRC that develop from well-defined adenomatous precursor lesions. 19,29,31,35 In contrast to the common prevailing belief in the United States that most CRC arise through a multistep genetic model of carcinogenesis, 45 starting from an adenomatous precursor lesion and ending with carcinoma (the adenoma-carcinoma pathway), some studies, particularly those of small, flat, and/or depressed neoplasms, have suggested that many ''small CRC'' do not arise from an adenomatous component and, thus, are considered ''de novo'' carcinomas.…”
mentioning
confidence: 99%
“…Cette proportion était de [29]. Les lésions plus évoluées étaient également localisées au niveau du côlon proximal, puisque parmi les carcinomes intramuqueux plans et polypoïdes respectivement 43 et 11 % étaient situés au niveau du côlon proximal, ces prévalences étant de 36 vs 11 % pour les carcinomes sous-muqueux superficiels [33].…”
Section: Cas Des Polypes Plansunclassified